The influence of birth date via body mass on individual fitness in a long‐lived mammal. Issue 6 (1st June 2015) - Plard, Floriane; Gaillard, Jean-Michel; Coulson, Tim; Hewison, A. J. Mark; Douhard, Mathieu; Klein, François; Delorme, Daniel; Warnant, Claude; Bonenfant, Christophe
Abstract : The timing of birth has marked impacts on early life and early development of newborns in many species. In seasonal environments, early‐born offspring often survive and grow better than late‐born offspring, but despite the long‐lasting effects of early conditions on life history traits, the influence of birth date on fitness has rarely been investigated for long‐lived species. In this study, we analyzed both the short‐ and long‐term effects of birth date on individual life history traits and explored its subsequent impact on individual fitness in a population of roe deer. We considered both the direct effects, as well as the indirect effects of birth date mediated through the effects of body mass, on demographic parameters. We found that in addition to short‐term effects on early body growth and survival, birth date generates "silver spoon" effects on adult life history traits of female roe deer. Birth date had long‐lasting effects on female adult body mass such that early‐born females were, on average, 3 kg heavier as adults than late‐born females, although female adult survival was similar between these categories. Based on the observed relationships between birth date, body mass, and demographic parameters, we built an integral projection model describing the simultaneous distributions of birth date and body mass to quantify the fitness consequences of birth date. We found that the fitness of early‐born females was higher than that of late‐born females. These long‐lasting effects of birth date on fitness were mostly mediated through the influence of birth date on recruitment and adult body mass. By determining development of newborns during the early stages of life, birth date has a critical influence on each step of an individual's subsequent life history trajectory.